Museu e Patrimônio das culturas afrodiaspóricas - Silva Santos, Deborah; Miranda Freitas, Joseania; Nascimento Bernardo da Cunha, Marcelo (Museologia & Interdisciplinaridade, 2022)
Apresentação do Dossiê "Museu e Patrimônio das culturas afrodiaspóricas"